Easy English Teaching in LEE Online Course - Wenny Pratiwi; Yeny Prastiwi (Universitas Muhammadiyah Yogyakarta, 2022)
The Corona Virus Disease (Covid-19) pandemic at the end of 2019 made people study or work from home to prevent the spreading of the Corona Virus. It made WhatsApp (instant messaging app) gain the most significant number of users during the pandemic. Learning English Easy (LEE), one of the online courses in Indonesia, uses WhatsApp as the primary tool in their teaching-learning process. It gained thousands of student participants with varied cultural backgrounds during its first year. A high enthusiasm of the participants towards LEE online course made the researchers want to describe its implementation of the teaching-learning process and inform the students' perception about the LEE Online Course as an alternative solution during the pandemic. The data were collected from interviews, questionnaires, observation, and documentation. The total participants in this research were 397 students and two stakeholders of LEE. The data analysis technique was done using descriptive interpretive of TPACK framework by Mishra and Koehler (2006). Based on the data analysis, the great combination of three elements: technology, pedagogy, and content knowledge, which were implemented by LEE online course, could manage thousand of participants at one time, and it gave a great outcome based on the students' perception.